Recent progress in the molecular imaging of therapeutic monoclonal antibodies - Kaifeng He; Su Zeng; Linghui Qian (Elsevier, 2020)
Therapeutic monoclonal antibodies have become one of the central components of the healthcare system and continuous efforts are made to bring innovative antibody therapeutics to patients in need. It is equally critical to acquire sufficient knowledge of their molecular structure and biological functions to ensure the efficacy and safety by incorporating new detection approaches since new challenges like individual differences and resistance are presented. Conventional techniques for determining antibody disposition including plasma drug concentration measurements using LC-MS or ELISA, and tissue distribution using immunohistochemistry and immunofluorescence are now complemented with molecular imaging modalities like positron emission tomography and near-infrared fluorescence imaging to obtain more dynamic information, while methods for characterization of antibody's interaction with the target antigen as well as visualization of its cellular and intercellular behavior are still under development. Recent progress in detecting therapeutic antibodies, in particular, the development of methods suitable for illustrating the molecular dynamics, is described here.